Teacher’s Roles As: Classroom Manager And Classroom Instructor - Oratmangun, Rendy (Publikasi Indonesia, 2021)
This descriptive quantitative study was intended to analyze and describe the the respondents’ perception of their teacher’s two classroom roles, namely manager and instructor. This study also examined the relationship of each role and different perception based on the respondents’ gender. There were 20 male students and 22 female students responded to the self-constructed questionnaire which was designed to evaluate one female English teacher. The results showed that this female English teacher was perceived as an effective English teacher who had played her roles in the classroom such a way that she was able to meet her student expectations. Next, each of the teacher’s role was significantly correlated with her other roles. The teacher’s two roles were found to be significantly correlated with each other. They all gave indication that when one role was played well, it would give influence on the increase of the level of other roles. These correlations implied that the teacher’s teaching competencies were already integrated in one personality. Finally, the finding showed that the students perception of their female teacher’s roles in the classroom had no gender bias, despite its commonality in education when perspectives are measured across opposite and same genders.